Epidemiological features, management, and consequences of sexual abuse at the General Reference Hospital of N’djili (Kinshasa/DRC) - BOMBA DI MASUANGI, Emmanuel; Atuba, P.; Mulumba, S.; Nsingi, A.; Mokili, Y.; Sifa Wabuza, R.; Sefu Wissa, C. (Orapuh Journal, 2025)
Introduction Sexual violence is a major public health issue with immeasurable consequences for survivors. In the Democratic Republic of Congo (DRC), sexual violence is strongly linked to armed conflicts, particularly in the eastern regions, where several studies have been conducted. However, less is known about the situation in the western part of the country. Purpose This study aimed to describe the epidemiological features, management, and health outcomes of sexual violence cases at the N’djili General Reference Hospital (HGR N’djili). Methods This was a retrospective descriptive study involving 483 consecutive survivors of sexual violence received at HGR N’djili between January 1 and December 31, 2021. Data were analysed using SPSS version 21. Qualitative variables were expressed as percentages, and quantitative variables as means with standard deviations. Results The mean age of survivors was 15.1 ± 5.4 years. The prevalence was higher among women (99.2%) than men. Rape was the main type of sexual violence (84.7%). The perpetrators had a mean age of 24.3 ± 10.2 years; 96% were male, of whom 82.4% were known to the victims (39.9% boyfriends, 20.1% neighbours, and 6.8% family members). Unintended pregnancies were recorded in 7.9% of cases, and HIV testing was positive in seven victims (1.5% of 475 tests performed). Victims were mainly referred to the care centre by the Public Prosecutor’s Office (37.7%) and the Congolese National Police (32.9%). Conclusion Sexual violence remains a serious public health problem, given the associated health outcomes, including sexually transmitted infections, HIV infection, hepatitis B virus, and unintended pregnancies. The survivors were mainly women and minors.